The Anthropometric Profile, Energy Expenditure and Level of Physical Activity in Goiânia High School Students: A Cross-Sectional Observational - Lucena Marquez, Roseane (2021)
Introduction: In adolescents, the prevalence of overweight and obesity, inadequate nutrition, associated with low levels of physical activity are risk factors for chronic diseases. It is emphasized that habits and behaviors formed in children and adolescents are reflected in adulthood. Objective: To describe the anthropometric profile, the physical activity level, and the energy expenditure of high school students in Goiânia. Methods: Descriptive observational cross-sectional study conducted with 347 high school students (181 males and 166 females), aged between 14 and 18 years, who underwent anthropometric assessment of height, body mass, waist and abdomen circumferences, body composition, classification of the level of physical activity and estimation of energy expenditure. The Shapiro-Wilk normality test and Mann-Whitney test were used. Results: There were statistically significant differences between male and female school children for: body mass, waist and abdomen circumference, skinfolds sum, percentage of fat and absolute fat.  differences were observed for moderate, vigorous activities and total energy expenditure. Among the schoolchildren evaluated, 74.4% were physically active, with the male percentage (80.1%) higher than the female (68.1%). Conclusion: It was observed a greater energy expenditure in moderate, vigorous physical activity and total energy expenditure in male students, while a higher number of skinfolds, fat percentage and absolute fat was recorded in female students.